Jožef Stefan je objavljal v angleščini in francoščini - Južnič, Stanislav (Obzornik za matematiko in fiziko, 2022)
We present twenty translations of abbreviations of Stefan’s basic experimental research, which were published simultaneously with Stefan’s articles printed in German language. English translations were issued in "The London, Edinburgh, and Dublin Philosophical Magazine" and "Journal of Science". At least two of these studies were also published as French translations in Paris and Geneva.
Keywords: Andreas pl. Ettingshausen; Marian Koller; Philosophical Magazine; Stefanov problem; zgodovina fizike in kemije